Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Question: An arithmetic sequence has a common difference of $1$ and a geometric sequence has a common ratio of $3$. A new sequence is formed by adding corresponding terms of these two progressions. It is given that the second and fourth term of the sequence are $12$ and $86$ respectively. Find, in terms of $n$,

  1. the $n^{th}$ term,
  2. the sum of the first $n$ terms

of the new sequence.


  1. $n+1+3^n$.
  2. $\frac 1 2 n(n+3) + \frac{3}{2} 3^n - \frac{3}{2}$.

Working so far

I am stuck getting different values for $a$.

enter image description here

share|cite|improve this question
up vote 4 down vote accepted

The problem seems to be that you assume that the first term in both sequences is $a$.

Correct equations would be $$u_2=a+1+3b=12$$ $$u_4=a+3+27b=86$$ where $a$ denotes the initial term of the arithmetic progression and $b$ is the initial term of the geometric progression.

I guess you can take it from here. (I got b=3 and a=2.)

share|cite|improve this answer

After you solve system of equations from Martin's answer you will get $a_1=2$ and $b_1=3$, so you can express $u_n$ as:




Let's denote sum of the first n_th terms as $S_n$ .We may write following:

$S_n= \sum_{k=1}^n (k+1+3^k)=\sum_{k=1}^n (k+1)+\sum_{k=1}^n 3^k$

First sum you can calculate as arithmetic progression sum and second sum you can calculate as sum of geometric series .

share|cite|improve this answer

(i) the first sequence is: $u_n=u_0+n$

the second sequence is $v_n=v_0 \cdot 3^n$

so the new sequence is : $w_n=u_0+n+v_0 \cdot 3^n$

since $w_2=12$ and $w_4=86$
then $u_0+2+v_0\cdot9=12$ and $u_0+4+v_0\cdot81=86$
then $u_0=1$ and $v_0=1$

so $w_n=1+n+3^n$

(ii) $\sum\limits_{k=0}^{n-1}w_k = \sum\limits_{k=0}^{n-1}1+\sum\limits_{k=0}^{n-1} k+\sum\limits_{k=0}^{n-1}3^k = n-1 + n\cdot(n-1)/2 + (3^n-1)/2$

share|cite|improve this answer
I typeset your formulas, please check that I haven't introduced mistakes. You can use LaTeX formula typesetting pretty much as usual, just enclose your formulas in dollar signs. – t.b. Oct 8 '11 at 9:02

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.